PELATIHAN VIRTUAL LOCAL AREA NETWORK (VLAN) DAN ROUTING DI SEKOLAH SMK ADVENT - Sitohang, Sunarsan; Pangaribuan, Hotma (ASOSIASI IDEBAHASA KEPRI, 2025)
The development of technology has a very big impact on the world of education. Today's advanced technology is very helpful for humans in doing their work, so it must be applied to get its benefits. It is undeniable that there are still many educational worlds that are very reluctant to use technology. This reluctance can be caused by the lack of will to learn or inadequate facilities and the absence of motivation or training. Virtual Local Area Network (VLAN) is a logical grouping of users and equipment connected to a network that is connected to administratively designated ports on a switch without regard to the location of the switch. VLAN is a technology that allows a Local Area Network (LAN) to be divided into several different segments. VLAN also allows the merging of networks that are physically separated, but seem to be in the same segment. After the community service was carried out, it was seen that the students' knowledge had increased, marked by the results of the evaluation carried out at the end of each community service session in each topic of the material. The increase in students' understanding also increased in configuring VLANs, marked by the students' ability to do configuration exercises without any assistance from the community service. From this community service activity, it can be concluded that the community service went smoothly and the students' knowledge about Switches and VLANs increased.